2003
DOI: 10.1038/sj.bjc.6600698
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of positive peritoneal cytology in endometrial carcinoma confined to the uterus

Abstract: A retrospective analysis was performed to evaluate the prognostic significance of peritoneal cytology in patients with endometrial carcinoma limited to the uterus. A total of 280 patients with surgically staged endometrial carcinoma that was histologically confined to the uterus were examined clinicopathologically. The median length of follow-up was 62 (range, 12 -135) months. All patients underwent hysterectomy and salpingo-oophorectomy with selective lymphadenectomy, and only three patients received adjuvant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 23 publications
2
60
0
2
Order By: Relevance
“…However, this finding might also be explained by a disproportionate benefit derived from radiotherapy in patients with positive peritoneal cytology. Table 4 shows that similarly high survival rates (88 -94% 3 -5 year survival) in women with stage I and cytological stage IIIA cancer have been observed in series where, as in our study, the large majority of cytological stage IIIA patients underwent either pelvic radiotherapy or total pelvic lymphadenectomy (Kadar et al, 1992;Kasamatsu et al, 2003). In contrast, the relatively poor results reported by other investigators (64 -67% 3 -5 year survival) in cytological stage IIIA patients might be explained by the fact that in these studies, only a minority of patients received treatment to pelvic lymph nodes (Morrow et al, 1991;Obermair et al, 2001;Preyer et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, this finding might also be explained by a disproportionate benefit derived from radiotherapy in patients with positive peritoneal cytology. Table 4 shows that similarly high survival rates (88 -94% 3 -5 year survival) in women with stage I and cytological stage IIIA cancer have been observed in series where, as in our study, the large majority of cytological stage IIIA patients underwent either pelvic radiotherapy or total pelvic lymphadenectomy (Kadar et al, 1992;Kasamatsu et al, 2003). In contrast, the relatively poor results reported by other investigators (64 -67% 3 -5 year survival) in cytological stage IIIA patients might be explained by the fact that in these studies, only a minority of patients received treatment to pelvic lymph nodes (Morrow et al, 1991;Obermair et al, 2001;Preyer et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…As some studies have suggested that cytology is an important prognostic factor, while others did not (Grimshaw et al, 1990;Morrow et al, 1991;Kadar et al, 1992;Obermair et al, 2001;Preyer et al, 2002;Kasamatsu et al, 2003), the value of peritoneal cytology in the staging of endometrial cancer is still controversial (Kasamatsu et al, 2003). In this study, we evaluated the impact of positive peritoneal cytology on the survival of patients operated for endometrial carcinoma and treated with adjuvant brachytherapy and/or external radiotherapy.…”
mentioning
confidence: 94%
“…All five pointed in the same direction and suggested that positive peritoneal cytology is not an independent prognostic factor in endometrial cancer, that is, some studies showed no survival difference between stage I and cytological stage IIIA cancer (Grimshaw et al, 1990;Kadar et al, 1992;Kasamatsu et al, 2003;Tebeu et al, 2003) and others showed an important survival difference within stage IIIA patients, that is, significantly better prognosis of cytological stage IIIA patients over histological stage IIIA patients (Preyer et al, 2002;Tebeu et al, 2003). These studies had several shortcomings.…”
Section: Discussionmentioning
confidence: 98%
“…Several were not able to adjust for use of radiotherapy, making it difficult to estimate the effect of peritoneal cytology in itself (Grimshaw et al, 1990;Kadar et al, 1992;Preyer et al, 2002;Tebeu et al, 2003). Some studies included patients with cervical involvement, but did not adjust for the possible impact of this prognostic factor (Kadar et al, 1992;Preyer et al, 2002;Kasamatsu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation